Evaluation the Impact of Changing Patient Thickness on Treatment Dose Amount Given to Injured Area - AL-Suhbani, Musherah; Serag, Saif; Baghous, Nor El Houda; El Mahjoub, Chakir (Open Access Macedonian Journal of Medical Sciences, 2022)
Radiation therapy provides an appropriate radiation dose to tumors. The proportion of this dose varies according to the injured part and its location. Targeting the part affected by the tumor with an appropriate radiation dose requires high accuracy in measuring from the radiation source to the patient and the amount of dose. This treatment was applied using digital linear accelerators and computers to treat the tumor with radiation. In most cases, it is used chemotherapy, one of the standard cancer treatments. However, those doses affect the patient as it leads to loss of appetite, which negatively affects the patient's weight. The patient loses weight during treatment, and the affected area's thickness changes during a Computed Tomography (CT) scan of the body for treatment planning. This led to changes in dose distribution to the target area and adjacent organs (organs at risk). This study examines the impact of changes in the patient's treatment area thickness on both dose and Source Surface Distance (SSD). In this study, we apply five different parts of cancer (lung, prostate, uterus, rectum, and vulva) that were treated by the traditional method using a linear accelerator and using a one-dimensional beam. Furthermore, CT takes images of the affected area to locate the tumor and plan treatment. Also, XIO device is used to track the patient's thickness during treatment and take a three-dimensional (3D) image of the patient during daily treatment sessions. The obtained results showed that the changing in treatment area thickness between 0.5 - 2.3cm, led to a change in the distance from the source to the patient's body, where the percentage of change was from 0.43 to 2.67%. Furthermore, the results showed that the dose increase of the planning target volume (PTV) by 1.54%, prostate 0.13%, rectum 0.38%, and bladder 0.83%, when the treatment area decreased thickness to 1.47 cm for prostate cancer. Moreover, the clinical target volume (CTV) dose by 0.40%, PTV 3.65%, rectum 3.84%, and bladder 3.19% decrease when the treatment area thickness increase by 3.16 cm in cervical cancer. Thus, the dose changed for the affected organ significantly more than the reference dose.